(Re)Positioning in the Englishes and (English) Literacies of a Black Immigrant Youth: Towards a Transraciolinguistic Approach. Issue 3 (3rd July 2019) - Smith, Patriann
Abstract : Increasing evidence confirms that multilingual and multiethnic English-speaking students face challenges with Englishes and English literacies when they migrate between their home countries and the United States. These challenges faced by immigrant and transnational students involve their dialects, accents, and communication styles, which lead them to question their capacity to speak English appropriately and grapple with what it means to be successful users of English literacy. Although examinations of these students' Englishes and literacies often centralize language, it is not often that race and language are equally foregrounded to illustrate the effects of both elements in the literate practices of these youth, many of whom are students of color. This article draws on positioning theory to describe how a Black immigrant English-speaking adolescent undergoes shifts in her experiences that (re)position her as a literate user of Englishes. I illustrate how the individual and global analyses recommended by a raciolinguistic perspective reflected Jaeda's development of a transraciolinguistic approach that allowed her to persist with a sense of agency. Implications for teachers, educators, researchers are outlined.